Preoperative Cognitive Stratification of Older Elective Surgical Patients: A Cross-sectional Study. Issue 6 (December 2016) - Culley, Deborah J.; Flaherty, Devon; Reddy, Srini; Fahey, Margaret C.; Rudolph, James; Huang, Chuan Chin; Liu, Xiaoxia; Xie, Zhongcong; Bader, Angela M.; Hyman, Bradley T.; Blacker, Deborah; Crosby, Gregory
Abstract : (Abstracted from Anesth Analg, 123(1):186–192, 2016) In general, elderly patients (aged ≥65 years) do not fare as well as younger patients after elective surgery. Health providers are aware of a number of factors that may play a role in this situation, including sustained functional decline.